Application of boundary scanning to digital devices testable design - Биньковская, А.Б.; Котух, В.Г.; Мирошник, М.А.; Селевко, С.Н. (Radiotekhnika, 2012)
Application of boundary scanning methods to digital devices testable design is carried out. It is offered to use the JTAG test tools to develop custom functional test stands. It is shown that the use of JTAG-test reduces the cost and time of testing.